Assessing biodiversity within the range of Heleobia chimbaensis (Caenogastropoda: Cochliopidae) on the Atacama Desert coast. Issue 7 (21st July 2020) - Collado, Gonzalo A.; Fuentealba, Carmen G.; Cazzaniga, Néstor J.; Valladares, Moisés A.
Abstract : Heleobia is the most specious genus in the family Cochliopidae, in which many species are morphologically similar. Here we used morphological, microstructural and phylogenetic criteria to investigate species delimitation within the Heleobia chimbaensis complex on the Atacama Desert coast. The range included subdivided populations of the species, the subspecies Heleobia chimbaensis conica, and the allopatric snails from Los Perales, first recognized as a population of H. chimbaensis and more recently considered a candidate species of the group. Traditional shell characters, morphometric analysis, operculum, and protoconch were either uninformative or ambiguous to separate taxa. However, the phylogenetic analysis identified H. chimbaensis, H. chimbaensis conica and four additional populations of the species as a monophyletic group while the population from Los Perales was recovered as a distantly evolutionary significant unit for which the name Heleobia peralensis sp. nov. is provided here. While the geographic isolation and limited dispersal seem to have influenced the diversification and current distribution of H. chimbaensis in Atacama, the origin of Heleobia peralensis sp. nov. remains unclear because of uncertain relationships. A conservation status assessment according to IUCN criteria and NatureServe methodology suggests that both H. chimbaensis and Heleobia peralensis sp. nov. face a high risk of extinction. http://www.zoobank.org:pub:91770DA4-B16F-46AD-A6D6-9638065ED899